Music, competition and the Art de seconde rhétorique: The youthful chansons of Gilles Mureau and Philippe Basiron - Woetmann Christoffersen, Peter (Danish Yearbook of Musicology, 2017)
The cultivation of poetry in fixed forms, known as the Art de seconde rhétorique, was important to the leading classes of society in fifteenth-century France. Fluency in composing poems and in conversing on literary subjects was desirable as means to support social advance and recognition – not least among the ambitious strata of clerks, lawyers and merchants. This study wants to raise the question whether a similar desire to participate in the greater cultural field were part of the driving forces behind the composing of polyphonic chansons. The question is reviewed by examining the few preserved chansons from around 1470 by two composers who made their entire careers in the service of the church as singers and choirmasters. Gilles Mureau (c.1442–1512) was around 1470 well established in a life-long career at the Chartres cathedral, while the slightly younger Philippe Basiron (c.1448–1491) already had reached the pinnacle of his career as magister puerum of the Sainte Chappelle in Bourges, a position he apparently left in 1474. Both musicians presumably composed chansons in their youth only, in their twenties, and they demonstrate an acute awareness of the contemporary poetic scene. We can be quite sure that Mureau wrote his own texts and used the whole range of artful poetic skills, and when composing he had the performances by the choirboys in mind. Basiron reacted in his production to this sort of songs, among them one of Mureau’s, by borrowing and rewriting poetry and by transforming musical ideas into his own creations.